Increased tail length in the King's skink, Egernia kingii (Reptilia: Scincidae): An anti-predation tactic for juveniles? - Barr, James; Somaweera, R.; Godfrey, S.S.; Bateman, Bill (OXFORD UNIV PRESS, 2019)
Caudal autotomy is an adaptive, but costly, anti-predation strategy used by many lizard species. As predation risk varies with ontogenetic life stage, it can be predicted that the use of costly anti-predation mechanisms would also change if they are no longer required. Here we assess ontogenetic change in relative tail length and degree of caudal autotomy in the King's skink (Egernia kingii), a large skink endemic to Western Australia. We found that younger individuals invested more in relative tail length compared to older individuals, with younger individuals also having a higher degree of their tail consisting of regenerated tissue. This appears to reflect an ontogenetic shift in the risk of predation for this species, with larger, more mature individuals capable of actively defending themselves against certain predator types and therefore decreasing their reliance on a costly anti-predation strategy compared to juveniles.